Cellulase Pretreatment of Kappaphycus alvarezii polymer for Promising Medical Dressing Application - Rosyidah, Dyah Rika Ar; Ermavitalini, Dini; Koentjoro, Maharani Pertiwi; Isdiantoni; Prasetyo, Endry Nugroho (PROCEEDING SURABAYA INTERNATIONAL HEALTH CONFERENCE 2019, 2020)
Seaweed contains hydrocolloid polysaccharides which are useful for the application of wound dressing. The use of natural ingredients such as seaweed Kappahycus alvarezii requires pretreatment before it is applied. Pretreatment of seaweed Kappaphycus alvarezii flour was carried out using hydrolyzing enzyme called cellulase. The cellulase (EC 3.2.1.4) is an enzyme which could hydrolyze cellulose polymers thereby breaking β- 1,4 glycosidic bond into oligosaccharide and simple sugars. Meanwhile the cell wall of seaweed could as well be degraded partially by cellulase followed by releasing hydrocolloid polymers (carrageenan) from the inner layer of seaweed cell wall. The aims of this study is to determine the effect of enzymatic pretreatment on seaweed so that it can be useful for further research as one of the promising component in wound dressing. The result showed that the reducing sugar decreased in content of 0.5 mg /ml after enzymatic modification at 0.5 hours incubation time. The FTIR spectra showed shifting at several functional groups namely C-H, C-O-C and C=C.